The Implementation of The Punishment of Whipping In Aceh From A Legal and Human Rights Perspective - Ethan Martupa Sahat Marune, Abraham (Ridwan Institute, 2021)
The special autonomy authority of the Province of Nanggroe Aceh Darussalam in Indonesia in the enforcement of Islamic criminal law is considered controversial with regard to the formalization of the enforcement of Islamic law by making the punishment ('uqubat) of whipping the main crime. The use and application of whipping by certain groups are seen as a form of cruelty, torture, contrary to the sense of legal justice, and a violation of human rights in Aceh. The authors will discuss the punishment of whipping from a legal and human rights perspective. The results of the author's research found that how the law in Indonesia and related Islamic law regulates the whipping punishment applied in Aceh, as well as discusses and analyzes human rights theories in relation to the whipping punishment in force in Aceh. Based on research, the authors conclude that whip punishment in force in Aceh has been referred to the sources of Islamic law then concretized to Qanun and confirmed by the Supreme Court ruling, and still pay attention to things that do not violate human rights.